2017
DOI: 10.1103/physrevlett.119.079903
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Lattice Dynamics of EuO: Evidence for Giant Spin-Phonon Coupling [Phys. Rev. Lett. 116 , 185501 (2016)]

Abstract: This corrects the article DOI: 10.1103/PhysRevLett.116.185501.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…18,19 The experimental results, supported by first-principles theory, uncovered a giant and highly anisotropic spin-phonon coupling induced by the spin dynamics slightly above and well below the T C in bulk EuO. 20,21 Previous lattice dynamics studies of surfaces, thin films, interfaces, and multilayers revealed drastic modifications of their phonon density of states (PDOS) with respect to the bulk counterparts with the main features being an enhancement of the number of phonon states at low and high energy and suppression and shift of the peaks. [22][23][24][25][26][27] In EuO, such phonon anomalies, combined with the strong interaction between spins and lattice vibrations could potentially increase the probability for undesired spin flips thus reducing the degree of spin polarization along certain crystallographic directions.…”
Section: Introductionmentioning
confidence: 77%
See 4 more Smart Citations
“…18,19 The experimental results, supported by first-principles theory, uncovered a giant and highly anisotropic spin-phonon coupling induced by the spin dynamics slightly above and well below the T C in bulk EuO. 20,21 Previous lattice dynamics studies of surfaces, thin films, interfaces, and multilayers revealed drastic modifications of their phonon density of states (PDOS) with respect to the bulk counterparts with the main features being an enhancement of the number of phonon states at low and high energy and suppression and shift of the peaks. [22][23][24][25][26][27] In EuO, such phonon anomalies, combined with the strong interaction between spins and lattice vibrations could potentially increase the probability for undesired spin flips thus reducing the degree of spin polarization along certain crystallographic directions.…”
Section: Introductionmentioning
confidence: 77%
“…This figure demonstrates that the PDOS of sample S1 exhibits the main features of bulk EuO, 20 namely two peaks at 11 and 17 meV and a high energy cut-off around 22 meV. The solid/ red line marks the calculated PDOS of a strain-free EuO crystal 20 convoluted with the damped harmonic oscillator (DHO) function 40 with a quality factor Q = 8. This function accounts remarkably well for the phonon lifetime broadening that arises from strain-relaxation induced distribution of interatomic distances.…”
Section: Methodsmentioning
confidence: 92%
See 3 more Smart Citations